PENGARUH KOMPENSASI, KEPEMIMPINAN, DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA KARYAWAN (Studi Kasus Pada Pt Perinco Graha Lestari) - Riyanto, Danang; Kasmir, K (SWOT : Jurnal Ilmiah Ilmu Manajemen, 2019)
Especially Management Company Often Made Dizziness With Satisfaction Work Employee Who Low, Many Ways Were Done By Management To Make Employee Care Of Hired By A, Because It Will An Undesired Effect A Less Well If The Employee Get Out Often Gave Way To New, Which Results In Reorganization.Research Aims To Understand The Influence Of Between Compensation, Leadership, And Workplace With Satisfaction Work An Employee Of Pt.Perinco Graha Lestari. Data Collection Obtained By Prompting A Questionnaire To 52 People Employees Of Pt. Perinco Graham Lestari, Then Mixed With Using Spss 16, With The Results Of The Testing Of Hypotheses Indicate That There Has Been A Positive Influence And Significant Compensation Between, Leadership, And Workplace Work With Satisfaction Employees Simultaneously, And In Testing Third Partial Variable Compensation, Leadership, And Workplace Everything It Has Some Positive Effects And Significant Work With Satisfaction Of Employees